The Effectiveness of Acceptance and Commitment Therapy on Difficulties in Emotion Regulation and Distress Tolerance in Students with High Academic Stress - Mahmoud Soltani, Roghayeh; Foroozeshfar , Nahid; Samirigi , Fariborz (KMAN Counseling & Psychology Nexus, 2026)
The present study was conducted to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on difficulties in emotion regulation and distress tolerance among students with high academic stress. This was a quasi-experimental study with a pretest–posttest design and a two-month follow-up with a control group. The statistical population consisted of students at Islamic Azad University, Tonekabon Branch during the 2024–2025 academic year. After administering the Gadzella Student-Life Stress Inventory, students who obtained scores of 188 and above were identified as individuals with high academic stress. Subsequently, 30 eligible students were selected through purposive sampling and randomly assigned to two groups: an experimental group and a control group, with 15 participants in each group. The experimental group received Acceptance and Commitment Therapy during 10 sessions of 90 minutes each, whereas the control group received no intervention during this period. Data were collected using the Difficulties in Emotion Regulation Scale and the Distress Tolerance Scale. Data analysis was performed using the independent samples t-test, Fisher’s exact test, and two-way repeated measures analysis of variance in IBM SPSS Statistics version 26. The results indicated that the experimental and control groups did not differ significantly in terms of demographic characteristics. Furthermore, the results of the two-way repeated measures analysis of variance demonstrated that the interaction effect of group and time on difficulties in emotion regulation and distress tolerance was significant. Based on mean comparisons, scores for difficulties in emotion regulation decreased from pretest to posttest in the experimental group, while distress tolerance scores increased. These changes remained largely stable at the two-month follow-up stage, whereas no substantial changes were observed in the control group. Based on the findings of the study, Acceptance and Commitment Therapy can reduce difficulties in emotion regulation and increase distress tolerance in students with high academic stress. Therefore, the use of this approach in university counseling centers may be beneficial in helping students manage negative emotions and enhance their ability to tolerate stressful academic situations.